A positive trade-off: Emissions reduction and costs under Phase IV of the Emissions Trading System - Jan Eric Hagendorn; Benjamin Hattemer; Fotios Kalantzis (European Investment Bank (EIB), 2024)
This paper investigates the impact of the EU Emissions Trading System (ETS) on the manufacturing sector, a significant contributor to greenhouse gas emissions within the EU. The ETS, a market-based policy tool, imposes a cap on emissions while enabling firms to trade emission allowances. Allocation of free allowances varies across sectors based on their carbon leakage status, indicative of the risk of losing competitiveness and relocating production to regions with less stringent climate policies. Leveraging a natural experiment design that exploits this variability, we employ a panel regression analysis at the sectorial level spanning 2012 to 2022 to examine how ETS prices influence sectors' carbon efficiency, direct emissions, production and prices, while controlling for other confounding factors. By contrasting the effects of ETS prices between sectors transitioning from carbon leakage status to facing higher allowance costs in Phase IV and those retaining their status across Phases III and IV, we also determine potential disparities in ETS price impacts. Additionally, we shed light on the mechanism of investment through which the EU ETS induces firms to reduce their emissions by employing a mediation analysis. Our analysis reveals that elevated ETS prices foster carbon efficiency and emission reduction, with marginal effects on production and prices. Notably, this effect is more pronounced for sectors transitioning from free to auctioned allowances. We identify investment as a key channel, which mediates the effect of ETS prices on the carbon efficiency of firms. Thus, our findings suggest that a reduction in free allowances combined with escalating ETS prices, mediated by increased investment, can bolster the environmental performance of the EU manufacturing sector without significantly compromising its competitive position.
Keywords: 330; EU ETS; Phase IV; Joint impact analysis; Mediation analysis